The origin, objective and function of the ethical community in Kant´s ’Religion within the boundaries of mere reason’ - Quiroga, Noelia Eva (Anales del Seminario de Historia de la Filosofía, 2020)
In this paper, I study the conceptual origin and objective of the ethical community in Religion within the boundaries of mere reason, with the aim of understanding its role concerning Kant’s theory of radical evil and the highest good and its relationship with the political community. I will first show that radical evil makes the ethical community necessary. Secondly, I will argue that the aim all the members of the ethical community share is the highest good. Third, I will show that the highest social good of Religion is not the highest good of the First Critique. Lastly, I will enumerate some differences between the ethical and the political communities respectively and some conclusions regarding the political analogy.